Perbandingan Pengetahuan Ibu Balita Dalam Mengatasi Diare Sebelum dan Sesudah Penyuluhan di Desa Lingkis Kecamatan Jejawi Kabupaten OKI - Sarmalina Simamora; Indri Septiani (Jurusan Farmasi, Poltekkes Kemenkes Palembang, 2021)
Background: Diarrhoea is a disease that is still a reasonably high health problem in Indonesia. Especially in toddlers, low maternal knowledge can be detrimental and even cause death. The aims of this study to identify whether or not there is a comparison of the knowledge of mothers under five on how to deal with diarrhoea before and after counselling in Lingkis Village, Jejawi District, OKI Regency. Methods: This is the Pre-Experimental research with a One Group Pretest-Posttest design. This research was conducted in March- May 2021. The sample were all mothers of toddlers whose toddlers had or were having diarrhoea who came to the integrated service post (Posyandu) in Lingkis village totalling, 38 respondents. Jejawi District, OKI Regency. With the provision of counselling in statistical tests using Wilcoxon analysis. Results: From the results of the Pretest and Posttest questionnaires tested with Wilcoxon analysis, there was an increase in knowledge after counselling with a value of Sig.2-tailed = 0.000 (P<0.05). The average value of respondents before counselling was 55.26, and the average value of respondents after counselling was 76.31. Conclusion: There is an increase in the knowledge of mothers under five in dealing with diarrhoea after counselling in Lingkis Village, Jejawi District, OKI Regency